Mountains as Evolutionary Arenas: Patterns, Emerging Approaches, Paradigm Shifts, and Their Implications for Plant Phylogeographic Research in the Tibeto-Himalayan Region - Muellner-Riehl, Alexandra N. (Frontiers in Plant Science, 2019)
Recently, the “mountain-geobiodiversity hypothesis” (MGH) was proposed as a key concept for explaining the high levels of biodiversity found in mountain regions of the Tibeto-Himalayan region (THR), which comprises the Qinghai–Tibetan Plateau, the Himalayas, and the biodiversity hotspot known as the “Mountains of Southwest China” (Hengduan Mountains region). In addition to the MGH, which covers the entire life span of a mountain system, a complementary concept, the so-called “flickering connectivity system” (FCS) was recently proposed for the period of the Quaternary. The FCS focuses on connectivity dynamics in alpine ecosystems caused by the drastic climatic changes during the past ca. 2.6 million years, emphasizing that fragmentation and allopatric speciation are not the sole factors for accelerated evolution of species richness and endemism in mountains. I here provide a review of the current state of knowledge concerning geological uplift, Quaternary glaciation, and the main phylogeographic patterns (“contraction/recolonization”, “platform refugia/local expansion”, and “microrefugia”) of seed plant species in the THR. In addition, I make specific suggestions as to which factors future avenues of phylogeographic research should take into account on the basis of the fundamentals presented by the MGH and FCS, and related complementary paradigm shifts.